Coordination of Necessary and Permissive Signals by PTEN Inhibition for CNS Axon Regeneration - Zhang, Jie; Yang, Dakai; Huang, Haoliang; Sun, Yang; Hu, Yang (Frontiers in Neuroscience, 2018)
In the nearly 10 years since PTEN was identified as a prominent intrinsic inhibitor of CNS axon regeneration, the PTEN negatively regulated PI3K-AKT-mTOR pathway has been intensively explored in diverse models of axon injury and diseases and its mechanism for axon regeneration is becoming clearer. It is therefore timely to summarize current knowledge and discuss future directions of translational regenerative research for neural injury and neurodegenerative diseases. Using mouse optic nerve crush as an in vivo retinal ganglion cell axon injury model, we have conducted an extensive molecular dissection of the PI3K-AKT pathway to illuminate the cross-regulating mechanisms in axon regeneration. AKT is the nodal point that coordinates both positive and negative signals to regulate adult CNS axon regeneration through two parallel pathways, activating mTORC1 and inhibiting GSK3ββ. Activation of mTORC1 or its effector S6K1 alone can only slightly promote axon regeneration, whereas blocking mTORC1 significantly prevent axon regeneration, suggesting the necessary role of mTORC1 in axon regeneration. However, mTORC1/S6K1-mediated feedback inhibition prevents potent AKT activation, which suggests a key permissive signal from an unidentified AKT-independent pathway is required for stimulating the neuron-intrinsic growth machinery. Future studies into this complex neuron-intrinsic balancing mechanism involving necessary and permissive signals for axon regeneration is likely to lead eventually to safe and effective regenerative strategies for CNS repair.